0068 Occupational exposure to hand-transmitted vibration and risk of Dupuytren's contracture. (23rd June 2014) - Palmer, Keith T; D'Angelo, Stefania; Syddall, Holly; Griffin, Michael J; Cooper, Cyrus; Coggon, David
Abstract : Objectives: To assess the relation between Dupuytren's contracture and occupational exposure to hand-transmitted vibration (HTV). Method: We mailed a questionnaire to 21 201 subjects of working age, chosen randomly from the age-sex registers of 34 general practices in Great Britain and to 993 subjects randomly selected from military pay records. We asked about occupational exposure to 39 sources of HTV and about fixed flexion contracture of the little or ring finger. Analysis focused on men at work in the previous week, for whom estimates were made of average daily vibration dose ( A (8) r.m.s.). Associations with Dupuytren's contracture were estimated by Poisson regression, both for lifetime exposure to HTV and for exposures > A (8) of 2.8 ms −2 r.m.s.in the past week, with adjustment for age, smoking status, social class and manual activities. Results: Full information on the study variables was available for 4969 eligible men, including 72 men with a history of Dupuytren's contracture, 2287 with occupational exposure to HTV, and 409 with A (8) >2.8 ms -2 in the past week. RRs from occupational exposure were elevated 1.5-fold, and were higher still for A (8) >2.8 ms -2 (adjusted RR 2.85, (95% CI 1.3–5.97). Conclusions: Our findings suggest that risk of Dupuytren's contracture is importantly elevated in men with high levels of weekly exposure to HTV.